2018
DOI: 10.1111/jep.12967
|View full text |Cite
|
Sign up to set email alerts
|

The importance of data issues when comparing cystic fibrosis registry outcomes between countries: Are annual review FEV1 in the UK only collected when subjects are well?

Abstract: Rationale, aims and objectiveCross‐country comparisons of cystic fibrosis (CF) outcomes can potentially identify variation in care but are dependent on data quality. An important assumption is that the UK annual review FEV1 is only collected during periods of clinical stability. If this assumption does not hold, results of FEV1 comparisons may be biased in favour of registries with encounter‐based FEV1. We aimed to test the assumption that CF annual reviews in the UK are only performed during periods of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(42 reference statements)
0
6
0
Order By: Relevance
“…The unknown timing of the best FEV1 measure relative to the other measures would also present additional challenges for the analysis. According the Registry protocol, annual reviews take place at a time when the patient is stable, and ongoing validation procedures indicate good adherence to this protocol [28]. Furthermore, there is no evidence to suggest that those receiving DNase are more likely to have their annual review during an unstable period compared to those not receiving DNase, meaning that using the FEV 1 measure obtained during the annual assessment should not result in any bias.…”
Section: Discussionmentioning
confidence: 99%
“…The unknown timing of the best FEV1 measure relative to the other measures would also present additional challenges for the analysis. According the Registry protocol, annual reviews take place at a time when the patient is stable, and ongoing validation procedures indicate good adherence to this protocol [28]. Furthermore, there is no evidence to suggest that those receiving DNase are more likely to have their annual review during an unstable period compared to those not receiving DNase, meaning that using the FEV 1 measure obtained during the annual assessment should not result in any bias.…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that annual review %FEV 1 underestimates lung health of adults in comparison with %FEV 1 captured during periods of clinical stability, which is an important systematic bias to consider for cross‐country comparisons against registries with encounter‐based FEV 1 . In this manuscript, we extended our previous work and analysed centre‐by‐centre discrepancy between paired annual review and best %FEV 1 to determine if systematic bias in annual review FEV 1 also affects between‐centre comparisons within the United Kingdom.…”
Section: Discussionmentioning
confidence: 83%
“…There has been a move by the UK CF registry towards comparisons using best FEV 1 data (which may be more reliable than annual review FEV 1 ), and it is encouraging that in the 2017 registry annual data report, 25/28 (89%) of centres now have ≥80% completeness for best FEV 1 data . Nonetheless, “best FEV 1 ” reported to the registry could still underestimate the lung health of people with CF if these data did not reliably select the highest FEV 1 from all FEV 1 readings over a 1‐year period . Identification of best FEV 1 data is difficult if data collectors are required to manually extract these data from routine clinical record, particularly in larger centres.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations